PERAN LAYANAN BIMBINGAN DAN KONSELING DALAM PEMILIHAN KARIR PADA SISWA SMA - Azyzyfa, Qorifa Al (Jurnal Empati Bimbingan dan Konseling, 2023)
One of the developmental tasks of students, especially high school students, is the readiness of students to organize the future. Therefore, students need the right career plan so that students can choose a career according to their strengths and talent interests. Guidance and counseling as an integral part of the school whose purpose is to provide support and assistance to the student in the face of his developmental tasks. In career planning, there are two influencing factors. Namely in the form of internal factors (within the self) and external factors (outside the self). High school career guidance should be able to guide each student through developmental tasks in the direction of career development and direct students towards creativity and implementation of a set of options and plans to be established. This research is intended to describe the role of guidance and counseling services in the career selection of high school students.